Iron Intake and Its Correlation to Ferritin and Hemoglobin Level among Children Aged 24–36 Months in Jakarta in 2020 - Jessica Ferdi (World Nutrition Journal, 2021)
Introduction: Iron is essential for child’s development and growth. Children’s iron requirements are secured from daily food intake that might be affected by Covid-19 pandemic. This study aims to determine iron intake and its relationship with ferritin and hemoglobin levels as indicators of iron status among children in Jakarta.